Manajemen Perpustakaan Terhadap Literasi Peserta Didik - Sani, Ahmad; Al Qadri, Muhammad (LSM Catimore dan Sahabat Jl. Paya Ilang/Pertamina Desa Lemah Burbana, Takengon, Aceh Tengah 24552, 2024)
This research is motivated by the factors that support and hinder students' reading interest, as well as to find out strategies that can increase students' reading interest. This study aims to understand how library management influences the reading culture among students, as well as the benefits of implementing library management for students. This research uses a literature review method, which is a systematic approach to collecting, analyzing, and synthesizing literature relevant to the topic of library management and its impact on student literacy. The research results show that maintenance and care of library materials influences students' reading interest. Therefore, the library organizational structure needs to manage the contents of the library, such as classifying each book and arranging the books neatly, as well as caring for and maintaining the books so that they remain suitable for reading. Furthermore, the literacy movement in schools does not only involve reading and writing, but also includes thinking skills according to the stages and components of literacy.